Preparation method of enhanced semi-solid slurry

By heating, applying ultrasonication and passing carbon dioxide gas into the aluminum alloy substrate, graphene and alumina are formed, and generated in situ through the self-propagation reaction of SiC particles, uniformly distributed on the surface and inside of the graphene, the semi-solid slurry is solved The problem of insufficient material strength and hardness has achieved a significant improvement in hardness and strength.

CN119433257APending Publication Date: 2025-02-14GUANGZHOU ZHONGSHAN FASTENER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411628836.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When studying semi-solid slurries, the prior art focuses on fluidity and dispersion, and pays less attention to its strength and hardness, resulting in insufficient mechanical properties when applied to automobiles, aerospace and other fields.

Method used

By heating the aluminum alloy substrate to a temperature above the liquid phase temperature, ultrasonication is applied and carbon dioxide gas is passed into the appropriate flow rate, graphene and alumina are formed, and generated in situ by the self-propagation reaction of SiC particles, uniformly distributed on graphite olefin surface and interior.

Benefits of technology

It significantly improves the hardness and strength of semi-solid aluminum alloy castings, broadens its application range, and has a wider application prospect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of preparation of semi-solid slurry, in particular to a preparation method of enhanced semi-solid slurry. According to the preparation method, SiC particles are generated in situ through a self-propagating reaction in a system which is at a proper temperature and provides proper dispersion force, and the SiC particles and aluminum oxide powder are uniformly distributed on the surface of graphene, so that on one hand, the growth of graphene is limited to form thin-layer graphene; and on the other hand, the SiC powder and the aluminum oxide powder can be uniformly distributed in the semi-solid slurry along with the graphene, so that the reinforcing performance of SiC can be fully played, the semi-solid alloy slurry in which SiC, graphene and aluminum oxide are uniformly distributed is obtained, and finally the semi-solid aluminum alloy casting with the hardness and strength obviously improved is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of semi-solid slurry preparation, and in particular to a method for preparing an enhanced semi-solid slurry. Background Art

[0002] Semi-solid slurry is a state of metal material between liquid and solid. From a microscopic perspective, it contains a certain proportion of solid particles and liquid metal. The solid particles are usually dendrite fragments or equiaxed crystals, which are suspended in the liquid metal matrix. For example, in the semi-solid slurry of aluminum alloy, there will be solid α-Al grains (equiaxed crystals) distributed in the aluminum liquid.

[0003] Since the fluidity of semi-solid slurry is between liquid and solid, this characteristic enables semi-solid slurry to fill complex mold cavities at lower pressure, and the molding pressure is also lower, which greatly saves preparation costs and can meet the requirements of product quality, performance and production efficiency.

[0004] From the perspective of preparation technology, semi-solid slurry can be prepared in many ways, such as mechanical stirring method - during the solidification process of liquid metal, a mechanical stirrer is used to stir it, break the growing dendrites, and form a semi-solid slurry; electromagnetic stirring method - by applying an alternating magnetic field, the liquid metal generates an induced current, and then forms convection under the action of electromagnetic force, which can also prepare semi-solid slurry. These methods are all aimed at controlling the solidification process of the metal so that it forms a special organizational form of semi-solid.

[0005] However, existing research on semi-solid slurries is mostly limited to the examination of fluidity and dispersibility, and there are few examinations on strength and hardness. With the continuous advancement of materials science, semi-solid slurries have increasingly broad application prospects in many fields including automobiles, aerospace, etc., which poses new challenges to the mechanical properties of semi-solid slurries.

[0006] Based on this, it is of great significance to develop semi-solid materials with high strength and hardness. Summary of the invention

[0007] In order to further improve the hardness and strength of the semi-solid slurry, the technical solution of the present application is specially proposed.

[0008] The technical solution of this application includes the following contents: A method for preparing an enhanced semi-solid slurry comprises the following steps: Heating an aluminum alloy substrate to a first temperature to obtain an aluminum alloy melt; the aluminum alloy substrate contains 4 wt% to 6 wt% Si, and the first temperature is higher than the liquidus temperature of the aluminum alloy substrate and the temperature difference is 10° C. to 20° C.; At the first temperature, applying a first dispersing force to the aluminum alloy melt and introducing a carbon-containing gas at a first flow rate, to obtain the enhanced semi-solid slurry after a first period of time; Wherein, applying the first dispersing force includes applying ultrasound, the first flow rate is 1 L / min~5 L / min, and the first time is 10 min~30 min.

[0009] In some embodiments, the temperature difference between the first temperature and the liquidus temperature of the aluminum alloy substrate is 15° C. to 20° C.

[0010] In some embodiments, the aluminum alloy substrate contains 6 wt % Si.

[0011] In some embodiments, the power of ultrasound is 1.5 kW to 2.5 kW, and the frequency is 15 kHz to 25 kHz.

[0012] In some embodiments, during the step of applying a first dispersing force to the aluminum alloy melt and introducing a carbon-containing gas at a first flow rate, the solid phase fraction of the aluminum alloy melt is monitored in real time, and the reaction is stopped when the monitored solid phase fraction reaches 30%, thereby obtaining the enhanced semi-solid slurry.

[0013] In some embodiments, the carbon-containing gas comprises carbon dioxide.

[0014] In some embodiments, the aluminum alloy substrate further includes at least one of Mg, Ti, and Sr.

[0015] In some embodiments, the aluminum alloy substrate includes 4 wt % to 6 wt % Si, 91 wt % to 95 wt % Al, 0.25 wt % to 0.45 wt % Mg, 0.08 wt % to 0.2 wt % Ti, and 0.01-0.02 wt % Sr.

[0016] In some embodiments, the aluminum alloy substrate has Fe≤0.2%, Mn≤0.1%, Zn≤0.07%, and other inevitable impurities≤0.15%.

[0017] On the other hand, the present application provides an enhanced semi-solid slurry, which is prepared by the preparation method described above.

[0018] The method for preparing the enhanced semi-solid slurry of the embodiment of the present application is to introduce carbon dioxide gas at a suitable flow rate into an aluminum alloy melt containing 4wt%~6wt% of Si at a suitable temperature, so that aluminum and carbon dioxide produce graphene and aluminum oxide under the high temperature and high pressure environment provided by ultrasonic cavitation, and at the same time, the graphene and Si in the aluminum alloy melt can further react to produce SiC particles, and the SiC particles are in situ generated by a self-propagating reaction and are evenly distributed on the surface of the graphene with the aluminum oxide powder. On the one hand, the growth of graphene is restricted to form a thin layer of graphene, and on the other hand, the SiC powder and the aluminum oxide powder can be evenly distributed in the semi-solid slurry with the graphene, so that the enhancement performance of SiC is fully exerted, thereby obtaining a semi-solid alloy slurry in which SiC, graphene and aluminum oxide are evenly distributed, and finally a semi-solid aluminum alloy casting with significantly improved hardness and strength is obtained.

[0019] The enhanced semi-solid slurry of the embodiment of the present application has significantly improved strength and hardness compared to traditional semi-solid slurries, broadens the scope of application, and has broader application prospects.

[0020] The details of one or more embodiments of the present application are set forth in the description which follows, and other features, objects, and advantages of the present application will be apparent from the description and its claims. DETAILED DESCRIPTION

[0021] The present application will be further described below in conjunction with the embodiments and examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. In addition, it should be understood that after reading the content taught in the present application, those skilled in the art may make various changes or modifications to the present application, and these equivalent forms also fall within the protection scope of the claims attached to the present application.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0023] the term Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings: The term "and / or" used in this article includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the arbitrary and all combinations include any two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in this application, the technical solution undoubtedly includes technical solutions that are all connected by "logical and", and undoubtedly includes technical solutions that are all connected by "logical or". For example, "A and / or B" includes three parallel solutions of A, B and A+B.

[0024] In the present application, "further" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0025] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0026] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the application purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0027] The technical features of the above-mentioned implementation modes and examples can be combined in any appropriate manner. To make the description concise, not all possible combinations of the technical features in the above-mentioned implementation modes and examples are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0028] In this application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges included therein.

[0029] In the present application, weight may be μg, mg, g, kg or other mass units known in the chemical industry.

[0030] In the present application, % (w / w) and wt% both represent weight percentage, % (v / v) refers to volume percentage, and % (w / v) refers to mass volume percentage.

[0031] In one aspect of the present application, a method for preparing an enhanced semi-solid slurry is provided, comprising the following steps: S100: heating the aluminum alloy substrate to a first temperature to obtain an aluminum alloy melt; the aluminum alloy substrate contains 4wt% to 6wt% Si, and the first temperature is higher than the liquidus temperature of the aluminum alloy substrate and the temperature difference is 10°C to 20°C; S200: applying a first dispersing force to the aluminum alloy melt at a first temperature and introducing a carbon-containing gas at a first flow rate to obtain an enhanced semi-solid slurry after a first period of time; Optionally, applying the first dispersing force includes applying ultrasound, the first flow rate is 1 L / min to 5 L / min, and the first time is 10 min to 30 min.

[0032] In the technical solution of the embodiment of the present application, at a suitable temperature, carbon dioxide gas is introduced at a suitable flow rate into an aluminum alloy melt containing 4wt% to 6wt% of Si, so that aluminum and carbon dioxide can produce graphene and aluminum oxide under the high temperature and high pressure environment provided by ultrasonic cavitation. At the same time, graphene and Si in the aluminum alloy melt can further react to produce SiC particles.

[0033] SiC particles can be used as reinforcing agents to improve the hardness and strength of alloy castings. However, SiC particles in the prior art are difficult to be evenly distributed during the preparation of semi-solid slurry and are easily pushed to the boundary by larger primary phases, making it difficult to exert their reinforcing effect.

[0034] In the technical solution of the embodiment of the present application, in a system with suitable temperature and providing suitable dispersing force, SiC particles are in-situ generated by self-propagating reaction and are evenly distributed on the surface of graphene with alumina powder. On the one hand, the growth of graphene is restricted to form a thin layer of graphene, and on the other hand, SiC powder and alumina powder can be evenly distributed inside the semi-solid slurry with graphene, so that the reinforcing properties of SiC can be fully exerted, thereby obtaining a semi-solid alloy slurry in which SiC, graphene and alumina are evenly distributed, and finally a semi-solid aluminum alloy casting with significantly improved hardness and strength is obtained.

[0035] In step S100, the aluminum alloy substrate is heated to a first temperature, which is higher than the liquidus temperature of the aluminum alloy substrate and has a temperature difference of 10°C to 20°C. Too high a temperature will lead to energy waste, and too low a temperature may cause dendrites due to uneven temperature.

[0036] The liquidus temperature refers to the temperature at which the alloy material changes from a completely liquid state to a solid-liquid coexistence state. This temperature is usually a range. The liquidus temperature in this article refers to the maximum value of the range. For example, the liquidus temperature of A356 aluminum alloy is usually between 570°C and 610°C. The liquidus temperature refers to the temperature range at which the A356 aluminum alloy changes from a completely liquid state to a solid-liquid coexistence state. The liquidus temperature in this article is based on 610°C. In the following provision "the temperature difference between the first temperature and the liquidus temperature of the A356 aluminum alloy is 15°C~20°C", the first temperature refers to a temperature range higher than 610°C and with a temperature difference of 15°C~20°C, that is, 625°C~630°C.

[0037] In one embodiment, the temperature difference between the first temperature and the liquidus temperature of the aluminum alloy substrate is 15° C. to 20° C. Optionally, the temperature difference between the first temperature and the liquidus temperature of the aluminum alloy substrate is 15° C., 16° C., 17° C., 18° C., 19° C., 20° C., etc.

[0038] The aluminum alloy substrate of the present application contains 4wt% to 6wt% Si, which ensures that sufficient raw materials are provided for forming SiC particles. However, the Si content should not be too high, otherwise too many SiC particles may agglomerate in the aluminum alloy, which will reduce the uniformity of the composite material and lead to uneven distribution of material properties.

[0039] In one embodiment, the aluminum alloy substrate contains 6 wt % Si.

[0040] In one embodiment, the aluminum alloy substrate further includes at least one of Mg, Ti and Sr.

[0041] In one embodiment, the aluminum alloy substrate includes 4wt%-6wt% Si, 91wt%-95wt% Al, 0.25wt%-0.45wt% Mg, 0.08wt%-0.2wt% Ti, and 0.01-0.02% Sr.

[0042] In one embodiment, the aluminum alloy substrate contains Fe≤0.2%, Mn≤0.1%, Zn≤0.07%, and other inevitable impurities≤0.15%.

[0043] In step S200, a first dispersing force is applied to the aluminum alloy melt at a first temperature (10°C to 20°C above the liquidus temperature) and a carbon-containing gas is introduced at a first flow rate to obtain an enhanced semi-solid slurry after a first period of time.

[0044] In this step, carbon dioxide gas is introduced into the aluminum alloy melt at a first temperature at a suitable flow rate, and aluminum and carbon dioxide produce graphene and aluminum oxide under the high temperature and high pressure environment provided by ultrasonic cavitation. At the same time, graphene and Si in the aluminum alloy melt can further react to produce SiC particles. The SiC particles are in-situ generated by a self-propagating reaction and are evenly distributed on the surface of the graphene with the aluminum oxide powder. On the one hand, the growth of graphene is restricted to form a thin layer of graphene. On the other hand, the SiC powder and the aluminum oxide powder can be evenly distributed in the semi-solid slurry with the graphene, so that the reinforcing properties of SiC are fully exerted, thereby obtaining a semi-solid alloy slurry in which SiC, graphene and aluminum oxide are evenly distributed, and finally a semi-solid aluminum alloy casting with significantly improved hardness and strength is obtained.

[0045] In this article, ultrasonic cavitation refers to the phenomenon that local gas or vapor cavities are formed in liquids due to strong sound waves, accompanied by the growth and collapse of these cavities. When ultrasound acts on liquids, tiny bubbles (cavitation nuclei) in the liquid absorb the energy of the sound waves, vibrate and expand. When the negative pressure half cycle of the sound wave acts on these bubbles, the bubbles will grow rapidly; while when the positive pressure half cycle of the sound wave acts, the bubbles are compressed and may eventually implode, releasing huge energy.

[0046] It is understandable that the introduction of ultrasound and carbon dioxide needs to be carried out simultaneously so that aluminum and carbon dioxide react fully, and the introduction rate of carbon dioxide affects the generation rate of graphene and aluminum oxide, and also affects the further reaction of graphene with Si in the aluminum alloy melt, that is, the generation rate of SiC particles. When carbon dioxide is introduced at an appropriate rate, SiC particles can be evenly distributed on the surface and inside of graphene through a self-propagating reaction, forming a strongly bonded embedded structure.

[0047] If the carbon dioxide introduction rate is too fast, the SiC particle generation rate is too fast, which may form aggregation and is not conducive to the synchronous formation with graphene, resulting in the SiC particles not being evenly distributed inside the graphene, and also over-constraining the layer thickness of the graphene, and failing to achieve the ideal strengthening effect; conversely, if the carbon dioxide introduction rate is too slow, resulting in the SiC particle generation rate being too slow, which is not conducive to constraining the layer thickness of the graphene, and also failing to achieve the ideal strengthening effect.

[0048] Optionally, in the embodiment of the present application, the first flow rate of introducing carbon dioxide is 1 L / min~5 L / min, for example 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, etc.

[0049] In step S200, the power of the ultrasound can be 1.5 kW to 2.5 kW, and the frequency can be 15 kHz to 25 kHz.

[0050] In some embodiments, the power of ultrasound is, for example, 1.5 kW, 1.6 kW, 1.7 kW, 1.8 kW, 1.9 kW, 2.0 kW, 2.1 kW, 2.2 kW, 2.3 kW, 2.4 kW, 2.5 kW, etc., and the frequency of ultrasound is, for example, 15 kHz, 16 kHz, 17 kHz, 18 kHz, 19 kHz, 20 kHz, 21 kHz, 22 kHz, 23 kHz, 24 kHz, 25 kHz, etc.

[0051] In step S200, in the step of applying a first dispersing force to the aluminum alloy melt and introducing a carbon-containing gas at a first flow rate, the solid phase fraction of the aluminum alloy melt is monitored in real time, and the reaction is stopped when the monitored solid phase fraction reaches 30%, thereby obtaining the enhanced semi-solid slurry.

[0052] In this article, solid fraction refers to the ratio of the volume of solid phase to the total volume of liquid-solid mixture when liquid and solid phase coexist. Common solid phase detection methods such as fiber Bragg grating (FBG) sensor measurement, ultrasonic propagation velocity method, differential scanning calorimetry (DSC) and other commonly used solid phase detection methods can be used for real-time detection.

[0053] In this paper, the solid phase fraction of the aluminum alloy melt reaches 30% in about 10-30 minutes. In this paper, it is necessary to ensure that the carbon dioxide and the aluminum alloy melt have sufficient reaction time, so a lower cooling rate is used.

[0054] In one embodiment, the carbon-containing gas includes carbon dioxide.

[0055] In yet another aspect of the present application, there is provided an enhanced semi-solid slurry, which is prepared by the preparation method described above.

[0056] The enhanced semi-solid slurry of the embodiment of the present application has significantly improved strength and hardness compared to traditional semi-solid slurries, broadened the scope of application, and has broader application prospects. For example, in the field of material processing, such as metal casting, it can be used for processes such as die-casting and thixoforming, and can manufacture parts with complex structures and high precision, effectively improve product quality and production efficiency, and reduce internal defects; in the construction industry, semi-solid slurries can be used in the preparation of new building materials, such as self-compacting concrete, which can self-level and fill formwork without vibration, thereby improving construction efficiency and the integrity of the building structure.

[0057] In some more specific embodiments, the enhanced semi-solid slurry of the embodiments of the present application is used to prepare parts in the automotive power system, such as the piston, connecting rod and other parts of the engine, and parts in the chassis system, such as steering knuckles, control arms, etc. The unique rheological properties and high strength and precision properties of the enhanced semi-solid slurry of the present application help to ensure the strength and precision of the parts during the molding process, so that these parts can withstand complex mechanical loads and ensure the stability and controllability of the car.

[0058] The following are some specific embodiments.

[0059] For experimental parameters not specified in the following specific embodiments, reference is made to the instructions given in the present application document, and reference may also be made to experimental manuals in the art or other experimental methods known in the art, or to experimental conditions recommended by manufacturers.

[0060] The raw materials and reagents involved in the following specific examples can be obtained from commercial sources, or can be prepared by those skilled in the art according to known methods.

[0061] Embodiment 1: This embodiment provides an enhanced semi-solid slurry (semi-solid slurry S1) of the present application, and the preparation steps include: (1) According to the composition of A356 aluminum alloy, various pure metals are weighed and placed in a crucible for mixing, wherein the Si content is 6w%; the mixed metals are heated and melted until the temperature reaches 10°C above the liquidus to obtain an aluminum alloy melt; (2) The temperature of the aluminum alloy melt was maintained at 10°C above the liquidus, and ultrasound (2 kW, 20 kHz) was applied thereto, while carbon dioxide was introduced at a rate of 5 L / min; the solid phase fraction was monitored in real time, and when the solid phase fraction was measured to be 30% (about 10 min of ventilation), the insulation and ventilation were stopped to obtain an enhanced semi-solid slurry.

[0062] Example 2: This example provides an enhanced semi-solid slurry (semi-solid slurry S2) of the present application, which is the same or similar to the preparation method of Example 1, except that: in step (1), the Si content is 4w%.

[0063] Example 3: This example provides an enhanced semi-solid slurry (semi-solid slurry S3) of the present application, which is the same or similar to the preparation method of Example 1, except that: in step (1), the mixed metal is heated and melted until it reaches 20°C above the liquidus to obtain an aluminum alloy melt.

[0064] Example 4: This example provides an enhanced semi-solid slurry (semi-solid slurry S4) of the present application, which is the same or similar to the preparation method of Example 1, except that: in step (2), the power of ultrasound is 10 kW.

[0065] Example 5: This example provides an enhanced semi-solid slurry (semi-solid slurry S5) of the present application, which is the same or similar to the preparation method of Example 1, except that: in step (2), ultrasound is applied to the aluminum alloy melt while stirring (2000 r / min), and the ultrasound conditions are the same as those in Example 1.

[0066] Example 6: This example provides an enhanced semi-solid slurry (semi-solid slurry S7) of the present application, which is the same or similar to the preparation method of Example 1, except that: in step (2), the introduction rate of carbon dioxide is 1 L / min.

[0067] Comparative Example 1: This comparative example provides a semi-solid slurry (semi-solid slurry D1), which is the same or similar to the preparation method of Example 1, except that: in step (1), the Si content of the aluminum alloy is 0.5%.

[0068] Comparative Example 2: This comparative example provides a semi-solid slurry (semi-solid slurry D2), which is the same or similar to the preparation method of Example 1, except that: in step (1), the Si content of the aluminum alloy is 10%.

[0069] Comparative Example 3: This comparative example provides a semi-solid slurry (semi-solid slurry D3), which is the same or similar to the preparation method of Example 1, except that: in step (2), ultrasound is not applied.

[0070] Comparative Example 4: This comparative example provides a semi-solid slurry (semi-solid slurry D4), which is the same or similar to the preparation method of Example 1, except that in step (2), nitrogen is introduced while applying ultrasound.

[0071] Comparative Example 5: This comparative example provides a semisolid slurry (semisolid slurry D5), which is the same or similar to the preparation method of Example 1, except that: in step (2), the ventilation rate of carbon dioxide is 0.5 L / min.

[0072] Comparative Example 6: This comparative example provides a semisolid slurry (semisolid slurry D6), which is the same or similar to the preparation method of Example 1, except that: in step (2), the ventilation rate of carbon dioxide is 10 L / min.

[0073] 2. Test Method The semi-solid slurry of each embodiment and comparative example was extruded into alloy castings by an extrusion die-casting machine, and hardness and strength tests were performed. The mechanical properties were tested on a Shimadzu AG-X100KN universal testing machine with reference to standard GB / T228.1. The test sample was processed into a dumbbell shape by wire cutting, and the upper and lower surfaces and sides were polished with 400-mesh sandpaper to eliminate the influence of defects on the experimental results. Three samples were tested at room temperature (25°C) at 1mm / min for each group of experiments and the average value was taken as the final test data. Hardness test was performed with reference to standard GB / T231.1.

[0074] The hardness was tested, and the specific test results are shown in the following table (Table 1).

[0075] Table 1 Mechanical properties test results of castings of semi-solid slurries of various embodiments and comparative examples

[0076] It can be seen from the above table that the samples of Examples 1 to 6 all have excellent mechanical strength. Among these examples, the improvement effects of the mechanical properties of Examples 1 to 3 and 6 are comparable, with tensile strength of 250 to 350 MPa, yield strength of 200 to 300 MPa, and hardness of 80 to 150 HRA. The improvement effect of the mechanical properties of Example 4 is relatively insignificant, mainly because the ultrasonic power of Example 4 is relatively high, resulting in too many cavitation bubbles, resulting in too many local high temperature and high pressure areas, resulting in excessive inhibition of graphene growth, affecting the tensile strength, yield strength and hardness. It is worth noting that the improvement effects of the tensile strength, yield strength and hardness of Example 5 are relatively more significant, mainly because stirring is added in Example 5, which is conducive to promoting uniform distribution of bubbles and sufficient contact of carbon dioxide, forming a more uniform SiC doping structure in graphene and alumina.

[0077] The content of Si in the sample of Comparative Example 1 is too low, and the prepared reinforcing agent SiC particles are relatively small, so the mechanical strength is poor. In the sample of Comparative Example 2, excessive Si is added to generate excessive SiC, which affects the uniformity of the aluminum alloy. Therefore, the mechanical strength improvement effect of the sample is not as good as that of the embodiment. In the preparation process of Comparative Example 3, ultrasound is not applied, and the mechanical properties of the prepared sample are relatively low. On the one hand, the sample cannot be evenly distributed during the preparation. On the other hand, the growth of graphene cannot be effectively restricted, and the expected thin-layer graphene cannot be obtained. In addition, this uneven distribution affects the internal dispersibility of SiC in the semi-solid slurry, resulting in a relatively low overall mechanical strength. In the sample of Comparative Example 4, Nitrogen is introduced, and no carbon source is provided, resulting in the inability to generate SiC, and an ordinary semi-solid alloy material is obtained, and the mechanical properties are not improved. In the sample of Comparative Example 5, the introduction rate of carbon dioxide is too fast, the generation rate of SiC particles is too slow, and the growth of graphene cannot be effectively controlled, and the improvement effect of mechanical properties is slightly worse than that of the embodiment. In the sample of Comparative Example 6, the introduction rate of carbon dioxide is too fast, the generation rate of SiC particles is too fast, and they cannot be evenly distributed, and the SiC particles generated too quickly excessively inhibit the growth of graphene, and also cause the SiC particles to agglomerate and cannot be evenly distributed inside or on the surface of graphene, so the improvement effect of mechanical properties is not good.

[0078] The above-described embodiments only express several implementation methods of the present application, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for those of ordinary skill in the art, without departing from the concept of the present application, several variations and improvements can also be made, which all belong to the protection scope of the present application. In addition, it should be understood that after reading the above-mentioned teaching content of the present application, those skilled in the art can make various changes or modifications to the present application, and the equivalent forms obtained also fall within the protection scope of the present application. It should also be understood that the technical solutions obtained by those skilled in the art on the basis of the technical solutions provided in the present application through logical analysis, reasoning or limited experiments are all within the protection scope of the claims attached to the present application. Therefore, the protection scope of the patent of the present application shall be based on the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A method for preparing an enhanced semi-solid slurry, characterized in that: The steps include: Heating an aluminum alloy substrate to a first temperature to obtain an aluminum alloy melt; the aluminum alloy substrate contains 4 wt% to 6 wt% Si, and the first temperature is higher than the liquidus temperature of the aluminum alloy substrate and the temperature difference is 10° C. to 20° C.; At the first temperature, applying a first dispersing force to the aluminum alloy melt and introducing a carbon-containing gas at a first flow rate to obtain the enhanced semi-solid slurry after a first period of time; Wherein, applying the first dispersing force includes applying ultrasound, the first flow rate is 1 L / min~5 L / min, and the first time is 10 min~30 min.

2. The method for preparing the enhanced semi-solid slurry according to claim 1, characterized in that: The temperature difference between the first temperature and the liquidus temperature of the aluminum alloy substrate is 15° C. to 20° C.

3. The method for preparing the enhanced semi-solid slurry according to claim 1, characterized in that: The aluminum alloy substrate contains 6 wt % of Si.

4. The method for preparing the enhanced semi-solid slurry according to any one of claims 1 to 3, characterized in that: The power of ultrasound is 1.5kW~2.5kW, and the frequency is 15kHz~25kHz.

5. The method for preparing the enhanced semi-solid slurry according to any one of claims 1 to 3, characterized in that: In the step of applying a first dispersing force to the aluminum alloy melt and introducing a carbon-containing gas at a first flow rate, the solid phase fraction of the aluminum alloy melt is monitored in real time, and the reaction is stopped when the monitored solid phase fraction reaches 30%, thereby obtaining the enhanced semi-solid slurry.

6. The method for preparing the enhanced semi-solid slurry according to any one of claims 1 to 3, characterized in that: The carbon-containing gas includes carbon dioxide.

7. The method for preparing the enhanced semi-solid slurry according to claim 1, characterized in that: The aluminum alloy substrate further includes at least one of Mg, Ti and Sr.

8. The method for preparing the enhanced semi-solid slurry according to claim 8, characterized in that: The aluminum alloy substrate includes 4wt% to 6wt% of Si, 91wt% to 95wt% of Al, 0.25wt% to 0.45wt% of Mg, 0.08wt% to 0.2wt% of Ti and 0.01-0.02% of Sr.

9. The method for preparing the enhanced semi-solid slurry according to claim 8, characterized in that: The aluminum alloy substrate contains Fe≤0.2%, Mn≤0.1%, Zn≤0.07%, and other inevitable impurities≤0.15%.

10. An enhanced semi-solid slurry, characterized in that: The enhanced semi-solid slurry is prepared by the preparation method according to any one of claims 1 to 9.